2009
DOI: 10.1007/s11517-009-0499-z
|View full text |Cite
|
Sign up to set email alerts
|

EEG inter/intra-hemispheric coherence and asymmetric responses to visual stimulations

Abstract: This study has attempted to increase the meaning and significance of findings in the experimental areas of electroencephalographic (EEG) visual or photic driving. The aim of this study was to investigate whether the visual stimulation at particular extremely low frequency order could possibly induce changes in the corresponding EEG frequency bands by examining the functional connectedness between brain regions. This was evaluated by applying the improved experimental protocol and objective using non-parametric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…This was evaluated by applying the improved experimental protocol and objective using a non-parametric spectral estimation coherence algorithm. The findings from our study revealed a significantly higher coherence in the EEG beta2 band (16.6 Hz) corresponding to 16.66 Hz visual stimulation, suggesting a high inter-hemispheric functional connectivity during visual stimulus (Cvetkovic & Cosic, 2009). A significant increase was revealed during 50 Hz visual stimulation at gamma band and a decrease during 4 Hz visual stimulation at theta band, linked with a substantial transitional shift in predominance from anterior to posterior relative power.…”
Section: Discussionsupporting
confidence: 51%
“…This was evaluated by applying the improved experimental protocol and objective using a non-parametric spectral estimation coherence algorithm. The findings from our study revealed a significantly higher coherence in the EEG beta2 band (16.6 Hz) corresponding to 16.66 Hz visual stimulation, suggesting a high inter-hemispheric functional connectivity during visual stimulus (Cvetkovic & Cosic, 2009). A significant increase was revealed during 50 Hz visual stimulation at gamma band and a decrease during 4 Hz visual stimulation at theta band, linked with a substantial transitional shift in predominance from anterior to posterior relative power.…”
Section: Discussionsupporting
confidence: 51%
“…This type of EEG synchronisation of driving alpha and beta EEG by alpha and beta sinusoidal MF stimulation, demonstrated in this study, could possibly be applied as therapeutic treatment(s) of particular neurophysiological abnormalities such as sleep and psychiatric disorders. In future, authors expect that the EEG synchronisation can effectively be demonstrated by either flickering of lights [10] and/or MF at ELF.…”
Section: Resultsmentioning
confidence: 99%
“…where, 𝐶𝑜ℎ 𝑥𝑦 𝑖𝑠 estimated coherence value in the range of 0-1 [33], f is frequency, 𝑊 𝑥 (𝑓) is the PSD of signal 𝑥, 𝑊 𝑦 (𝑓) is the PSD of signal 𝑦 and 𝑊 𝑥𝑦 (𝑓) is cross spectral density between the two brain region. If the coherence value approaches=1, it means that the x and y signals are similar.…”
Section: Eeg Coherencementioning
confidence: 99%